1998
DOI: 10.1002/(sici)1099-0720(1998120)12:6<593::aid-acp579>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status, social class and memory performance: a critical response to Herrmann and Guadagno (1997)

Abstract: Herrmann and Guadagno (1997) reviewed evidence concerning the relationship between memory performance and socio‐economic status (SES). As a measure of social stratification, SES is narrow and ethnocentric, and it ignores the role of social prestige, power and status. The selection of research for quantitative analysis and the measure of effect size used by Herrmann and Guadagno are criticized. Across the available corpus of studies, there is a highly significant relationship between SES and memory performance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Seamon et al (2002) suggested that hits and false alarms on recognition tests are based on gist memories for experience whereas performance on recall tests depends more on accessing verbatim traces of the presentation of individual targets. This raises the interesting possibility that the SES-related deficits in children's memories are localized within the ability to retrieve the meaning relations between targets, a suggestion consistent with the findings from Richardson's (1998) meta-analysis. This is also consistent with the observation that SES-related differences in memory could be the result of differences in prior experiences (see also Dartigues et al, 1992).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Seamon et al (2002) suggested that hits and false alarms on recognition tests are based on gist memories for experience whereas performance on recall tests depends more on accessing verbatim traces of the presentation of individual targets. This raises the interesting possibility that the SES-related deficits in children's memories are localized within the ability to retrieve the meaning relations between targets, a suggestion consistent with the findings from Richardson's (1998) meta-analysis. This is also consistent with the observation that SES-related differences in memory could be the result of differences in prior experiences (see also Dartigues et al, 1992).…”
Section: Discussionsupporting
confidence: 68%
“…As it turns out, SES differences in memory are reasonably well established. In a meta-analysis by Richardson (1998; see also Guadagno & Herrmann, 1998;Herrmann & Guadagno, 1997), it was shown that SES differences in memory are related to both what is being remembered (content) and the context in which it is being memorized. For example, Newcomb and Collins (1979) found that children of low SES remembered less about a television program with a White middle-class family than did children of middle SES but more about a program with an African American lower-class family even when the child viewer's ethnicity was controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Given that social forces, including social stratification, influence adult development indirectly through a variety of pathways (see Baltes, 1987;Featherman, Smith, & Peterson, 1990;Mayer, Maas, & Wagner, 1999), it is not prudent to assign any and all predictive power of social stratification variables to the construct of an engaged lifestyle. Indeed, Herrmann and Guadagno (1997) and Richardson (1998) recently discussed correlations of SES with memory performance in children and adults in terms of a number of hypothetical mediating mechanisms such as physical health, emotional adjustment, test anxiety, strategic behavior in the testing context, and familiarity with assessment contexts. Herrmann and Guadagno summarized the state of the literature as follows: "With so many hypotheses and so little systematic investigation, any conclusion about the positive correlation of SES and memory would be premature at this time" (p. 118).…”
Section: Measurement Of Engaged Lifestylementioning
confidence: 99%
“…There is also some evidence for sex differences in working memory and reaction times (DeLuca et al 2003 ; Meinz and Salthouse, 1998 ), with men having better cognitive performance on these tests than women. Additionally, higher socio-economic status has been associated with better cognitive function in later life (Herrmann and Guadagna, 1997 ; Richardson, 1999 ) and will be investigated as a potential predictor of memory in the current study.…”
Section: Introductionmentioning
confidence: 99%